2018
DOI: 10.5137/1019-5149.jtn.24773-18.1
|View full text |Cite
|
Sign up to set email alerts
|

Effect of curcumine on the formation of epidural fibrosis in an experimental laminectomy model in rats

Abstract: fat graft, collagen membrane, Adcon-L, and fibrinolytic agents but no effective treatment option was found (6,8,9,17,19,22). Curcumin (diferuloylmethane) gives turmeric its yellow color (the ground rhizome of Curcuma longa L.), and is often employed as a spice and is recognized for its anti-inflammatory features (1,16). Curcumin affects the nuclear factor kappa β (NF-κB) in pro-inflammatory cytokine reproduction, the antiapoptotic process, the functioning of leukocytes, and cell survival (1). AIM:To clarify th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…For the inhibition of specific inflammatory cytokines, etanercept, a TNF-α blocker, [1] tamoxifen, a TGF-β blocker, [7] methyl palmitate, [18] and dexmedetomidine [4] have been extensively investigated. Also, there are studies using diclofenac sodium [20] and curcumin [21] as anti-inflammatory agents. All these studies showed that both inflammatory cytokine inhibition and the use of anti-inflammatory agents significantly reduced the development of epidural fibrosis by producing anti-inflammatory and antioxidant effects.…”
Section: Discussionmentioning
confidence: 99%
“…For the inhibition of specific inflammatory cytokines, etanercept, a TNF-α blocker, [1] tamoxifen, a TGF-β blocker, [7] methyl palmitate, [18] and dexmedetomidine [4] have been extensively investigated. Also, there are studies using diclofenac sodium [20] and curcumin [21] as anti-inflammatory agents. All these studies showed that both inflammatory cytokine inhibition and the use of anti-inflammatory agents significantly reduced the development of epidural fibrosis by producing anti-inflammatory and antioxidant effects.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, an appropriately placed subdural gelatin sponge over cerebral tissue may prevent postoperative surgical adhesions after neurosurgical procedures [18]. However, it has been reported that gelatin sponges may be related to increased odds of epidural fibrosis [21][22][23], and care must be taken when they are used in confined space because of their absorption capability and the related swelling of the sponge.…”
Section: Gelatin Spongesmentioning
confidence: 99%
“…Laminectomy is a surgical procedure typically employed in the treatment of numerous spinal disorders such as lumbar disk herniation, spinal stenosis, and tumor excision [ 1 ]. Although this treatment is generally effective and relieves neural compression, 8–40% of patients suffer from failed back surgery syndrome (FBSS), with 4–9% undergoing revision surgery [ 2 , 3 ].…”
Section: Introductionmentioning
confidence: 99%